The 20th Asia and South Pacific Design Automation Conference 2015
DOI: 10.1109/aspdac.2015.7059112
|View full text |Cite
|
Sign up to set email alerts
|

IC Piracy prevention via Design Withholding and Entanglement

Abstract: Globalization of the semiconductor industry has raised serious concerns about trustworthy hardware. Particularly, an untrusted manufacturer can steal the information of a design (Reverse Engineering), and/or produce extra chips illegally (IC Piracy). Among many candidates that address these attacks, Design Withholding techniques work by replacing a part of the design with a reconfigurable block on chip, so that none of the manufactured chips will function properly until they are activated in a trusted facility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…3(a). Two symmetric groups of cells in the K-map always have the same binary distance structure defined in (12). One example of the group of cells that is symmetric to those for the Lf T in Fig.…”
Section: K-map Cell Selection For Non-complementary Functionsmentioning
confidence: 97%
See 3 more Smart Citations
“…3(a). Two symmetric groups of cells in the K-map always have the same binary distance structure defined in (12). One example of the group of cells that is symmetric to those for the Lf T in Fig.…”
Section: K-map Cell Selection For Non-complementary Functionsmentioning
confidence: 97%
“…The f and g in our design can be complementary as well. Select Lg T = [0, 1, 2, 3, 4, 5, 7] and Lf T = [6,8,9,10,11,12,13,14,15]. It can be found that Lf T i = 5 and Lg T j = 6 satisfy Constraint 1.…”
Section: Examplementioning
confidence: 99%
See 2 more Smart Citations
“…Scrambling the interconnection network in a permutation-based technique will cause the circuit to only work with a correct key which will configure the interconnection network [10]. Other work has hidden parts of the circuit in a configurable lookup table (LUT) [11]. With those obfuscation methods, the effort for an attacker to find the correct key will become computationally infeasible [12].…”
Section: Introductionmentioning
confidence: 99%